Pendampingan Persiapan UMKM Dalam Memperoleh Sertifikat PIRT Pangan Guna Meningkatkan Daya Saing Ditengah Pandemi Covid - 19 - abi hanif dzulquarnain; Prayudi Harianto (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
The target MSMEs are MSMEs engaged in culinary, which have eating outlets to sell their sales. Culinary dishes that are the mainstay menu are processed chicken and fish (catfish) which are then fried with crispy seasoning with green chili sauce. Recently MSME partners in this study launched Frozen food products which means that MSME partners think to reach the potential for purchasing food products not only in the form of fresh (eating in place or brought home). Considering the existence of packaging products sold to customers, so this needs attention, especially in the legalization and distribution permit of the product (PIRT). The focus of problem solving on mentoring activities is up to the issuance of NIB and IUMK by the One Door Integrated Investment Coordinating Board (BKPM - TSP) with an online system that uses the site www.oss.go.id, as the first administrative requirement of the UMKM business has a certificate of distribution. Product (PIRT). MSME partners in this study are worth referred to as micro businesses by showing the requirements and supporting evidence obtained during the mentoring period until the exit of the business ID number (NIB). MSME partners in this study are worth referred to as micro businesses by showing the requirements and supporting evidence obtained during the mentoring period until the business permit (IUMK).